Strategi Komunikasi Lembaga Pemasyarakatan Dalam Perubahan Perilaku Masyarakat Binaan Di Lembaga Pemasyarakatan Kelas Iia Sibolga Sumatera Utara - Fahri Hidayat Hasibuan; Yusuf Afandi (Lembaga Pengembangan Kinerja Dosen, 2023)
Achieving success, a government agency such as the Sibolga Class IIA Penitentiary which is engaged in fostering community development, must have a good communication strategy and must use the right method so that the coaching carried out can be accepted so that the assisted community after the expiration of their sentence can be accepted back into prison. society and also not to repeat the mistakes made. Fostered People who need appropriate approaches, to change their criminal behavior into human beings with good behavior. The effort needed as an approach is to provide information to humans regarding the meaning in the views and goals of humans living in the world, conveying what is right and what should be done and what is wrong and what cannot be done, using an approach or in this case a communication strategy that is appropriate to the mental condition of the inmates. In general, the purpose of communication is to expect the participation of the communicant on ideas or messages conveyed by the communicator. So that in the process there is a change in attitude and behavior that is expected. The type of research that the authors use in this study is to use a qualitative research approach. Qualitative research according to Sugiyono is a research method that is intended to understand phenomena about what is experienced by research subjects such as behavior, perceptions, motivations, actions, etc., by means of descriptions in the form of words and language, in a special natural context and with take advantage of natural methods. Research Results of Fostered Communities when carrying out coaching activities. And also the Sibolga Class IIA Penitentiary uses several mass media and print media as well as electronic media to convey messages to the Fostered Communities. The status barrier that occurs is that there are still assisted communities who view the status or position of Class IIA Sibolga Penitentiary officers when conveying messages or information, especially to carry out coaching activities so that assisted communities are lazy to take part in coaching activities.